x → ∞ lim ( x − 2 0 1 4 x 2 0 1 4 + x 2 0 1 3 )
If the limit above can be expressed as − b a for coprime positive integers a and b , find the value of a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Done it the same way. :) . You should mention that:
x → ∞ lim ( 1 + x 1 ) 2 0 1 4 1 = 1 + 2 0 1 4 x 1 + O ( x 2 1 )
We have: x → ∞ lim ( x − 2 0 1 4 x 2 0 1 4 + x 2 0 1 3 ) Take h = x 1 → 0 : = h → 0 lim ( h 1 − 2 0 1 4 h 2 0 1 4 1 + h 2 0 1 3 1 ) Take common factor: = h → 0 lim ( h 1 − 2 0 1 4 h 2 0 1 4 1 2 0 1 4 1 + h ) Simplify: = h → 0 lim ( h 1 − h 1 2 0 1 4 1 + h ) Take common factor: = h → 0 lim ( h 1 ( 1 − 2 0 1 4 1 + h ) ) = h → 0 lim ( h 1 ( 2 0 1 4 1 − 2 0 1 4 1 + h ) ) Using lemma below: = h → 0 lim ( h 1 × 2 0 1 4 1 2 0 1 3 + 2 0 1 4 1 2 0 1 2 ( 1 + h ) 1 + ⋯ + 2 0 1 4 ( 1 + h ) 2 0 1 3 ( 1 ) − ( 1 + h ) ) Expanding numerator: = h → 0 lim ( h 1 × 2 0 1 4 1 2 0 1 3 + 2 0 1 4 1 2 0 1 2 ( 1 + h ) 1 + ⋯ + 2 0 1 4 ( 1 + h ) 2 0 1 3 − h ) Cancelling: = h → 0 lim − 2 0 1 4 1 2 0 1 3 + 2 0 1 4 1 2 0 1 2 ( 1 + h ) 1 + ⋯ + 2 0 1 4 ( 1 + h ) 2 0 1 3 1 Substituting: = − 1 + 1 + ⋯ + 1 1
Lemma: x − y = ∑ i = 0 n − 1 x n − i − 1 y i x n − y n
There's a much shorter approach. Does this look familiar to you?
= h → 0 lim ( h 1 ( 2 0 1 4 1 − 2 0 1 4 1 + h ) )
Hint : Definition of derivative.
lim x → ∞ ( x − 2 0 1 4 x 2 0 1 4 − x 2 0 1 3 ) =
lim x → ∞ x ∗ ( 1 − ( 1 + x 1 ) 2 0 1 4 1 ) =
lim x → ∞ x ∗ ( 1 − ( ( 1 + x 1 ) 2 0 1 4 ) 1 − 1 ) =
lim x → ∞ x ∗ ( 1 − ( 1 + x 1 + 2 0 1 4 ∗ x 1 + ( 2 2 0 1 4 ) ∗ x 1 + … 1 ) − 1 ) = 2 0 1 4 − 1
Problem Loading...
Note Loading...
Set Loading...
L = x → ∞ lim ( x − 2 0 1 4 ( x 2 0 1 4 ) ( 1 + x 1 ) )
⇒ L = x → ∞ lim ( x − x ( 2 0 1 4 1 + x 1 ) )
Now as x → ∞ , x 1 → 0
⇒ x → ∞ lim ( 1 + x 1 ) 2 0 1 4 1 = 1 + 2 0 1 4 x 1 + O ( x 2 1 )
⇒ L = x → ∞ lim ( x − x ( 1 + 2 0 1 4 x 1 ) ) = − 2 0 1 4 1